A facile synthesis method for highly water-dispersible reduced graphene oxide based on covalently linked pyridinium salt - Shin, Dong Geun; Yeo, Hyeonuk; Ku, Bon-Cheol; Goh, Munju; You, Nam-Ho (PERGAMON-ELSEVIER SCIENCE LTD, 2017)
We simultaneously conducted reduction and functionalization processes on graphene oxide (GO) in order to obtain functionalized reduced GO (rGO). One of the main barriers to the development of rGO is its poor dispersibility in water and polar solvents. Nevertheless, the rGO synthesized in this study exhibits high dispersibility in water. In this research, we prepared GO by oxidizing graphite using the Hummers method, and it was functionalized by 4-pyridine moiety using 4-hydrazinylpyridine graphene (rGO-4Py). The rGO-4Py was further functionalized by methylation using methylpyridinium iodide, producing reduced graphene oxide (rGO-4Py-MeI). The resulting rGO-4Py-MeI exhibited good dispersion in water due to the effect of the pyridinium. The rGO-4Py-MeI's potential as a nanocomposite filler was evaluated by mixing it into water-soluble poly(vinyl alcohol) (PVA). The tensile strength and modulus of the resulting rGO-4Py-MeI/ PVA nanocomposites were measured for different loadings of rGO-4Py-Me. The PVA nanocomposite embedded with 1 wt % of rGO-4Py-MeI showed increases of 69% (88.77 MPa) and 86% (4.36 GPa) in tensile strength and tensile modulus compared to neat PVA, respectively. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: POLYMER NANOCOMPOSITES; CARBON NANOTUBES; POLYIMIDE NANOCOMPOSITES; ELECTRICAL-CONDUCTIVITY; COMPOSITES; NANOSHEETS; REDUCTION; GRAPHITE; FILMS